2022
DOI: 10.3389/fnmol.2022.906762
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Prognostic Role of Glia Maturation Factor-γ in Gliomas

Abstract: BackgroundGlia maturation factor-γ (GMFG) regulates actin cytoskeletal organization and promotes the invasion of cancer cells. However, its expression pattern and molecular function in gliomas have not been clearly defined.MethodsIn this study, public datasets comprising 2,518 gliomas samples were used to explore GMFG expression and its correlation with malignancy in gliomas. Immunohistochemistry (IHC) staining was performed to determine the expression of GMFG in gliomas using an in-house cohort that contained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Co-expression analysis revealed that in LGG, NDUFA6-DT exhibits a positive correlation with PHLPP2 [41] and GRIA2 [42], known for inhibiting glioma progression. In contrast, it demonstrates a negative correlation with GMFG [43], S100A6, and S100A11 [44], all of which are associated with promoting glioma progression. Similarly, in GBM, NDUFA6-DT demonstrates a negative correlation with SUMF1 [45], CD109 [46], MUC11 [47], and MYBPH [48], which are all implicated in promoting glioma progression.…”
Section: Discussionmentioning
confidence: 88%
“…Co-expression analysis revealed that in LGG, NDUFA6-DT exhibits a positive correlation with PHLPP2 [41] and GRIA2 [42], known for inhibiting glioma progression. In contrast, it demonstrates a negative correlation with GMFG [43], S100A6, and S100A11 [44], all of which are associated with promoting glioma progression. Similarly, in GBM, NDUFA6-DT demonstrates a negative correlation with SUMF1 [45], CD109 [46], MUC11 [47], and MYBPH [48], which are all implicated in promoting glioma progression.…”
Section: Discussionmentioning
confidence: 88%
“…Glia maturation factor (GMFG), primarily synthesized in inflammatory cells, is now recognized as a novel member of the actin depolymerization factor/cofilin superfamily of proteins [ 40 ]. Research indicates that GMFG plays a pivotal role in regulating the chemotaxis of neutrophils, lymphocytes, and monocytes, making it an integral component of the body's inflammatory response [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been shown to inhibit the growth of lung cancer by activating the p53 signaling pathway [ 50 ]. In the case of LGG, which exhibit higher levels of GMFG expression, it has been associated with worse overall survival [ 40 ]. Furthermore, GMFG has been found to play a critical role in the metastasis of epithelial ovarian cancer and colorectal cancer [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…TMZ is a first-line treatment for glioma, and the MGMT promoter methylation status is a factor that predicts therapeutic responses to TMZ. However, the accuracy of MGMT promoter methylation in predicting responses to TMZ is limited [ 32 ]. Our study found that glioma patients with high BCL2A1 expression had poor responses to TMZ treatment.…”
Section: Discussionmentioning
confidence: 99%